Organic waste recycling for carbon smart circular bioeconomy and sustainable development: A review. (September 2022) - Kumar Awasthi, Mukesh; Yan, Binghua; Sar, Taner; Gómez-García, Ricardo; Ren, Liheng; Sharma, Pooja; Binod, Parameswaran; Sindhu, Raveendran; Kumar, Vinod; Kumar, Deepak; Mohamed, Badr A.; Zhang, Zengqiang; et al.
Graphical abstract: Highlights: Overview of challenges and opportunities of low carbon circular bioeconomy. Development of low carbon circular bioeconomy were discussed. Co-evolution of ecosystems, technologies, business strategies and user practices was analyzed. Overview of value-added products production from these substrates were review. Metabolic pathway of acidogenic fermentation was reviewed. Abstract: The development of sustainable and low carbon impact processes for a suitable management of waste and by-products coming from different factors of the industrial value chain like agricultural, forestry and food processing industries. Implementing this will helps to avoid the negative environmental impact and global warming. The application of the circular bioeconomy (CB) and the circular economic models have been shown to be a great opportunity for facing the waste and by-products issues by bringing sustainable processing systems which allow to the value chains be more responsible and resilient. In addition, biorefinery approach coupled to CB context could offer different solution and insights to conquer the current challenges related to decrease the fossil fuel dependency as well as increase efficiency of resource recovery and processing cost of the industrial residues. It is worth to remark the important role that the biotechnological processes such as fermentative, digestive and enzymatic conversions play for an effective waste management and carbon neutrality.